Coverage of climate change information in Tanzanian newspapers - Siyao, P.O. & Sife, A.S. (2018) (2024)
Purpose – This study was conducted to analyse the extent at which Tanzanian newspapers paid attention to climate change information over the period of 10 years between January 2006 and December 2015. Design/methodology/approach – Six Tanzanian newspapers were quantitatively content analysed for frequencies of coverage to climate change information. Findings – The results indicate that of total six Tanzanian newspapers had very few (684; 0.84 per cent) articles on climate change which is an average of 68.4 articles per year. Much attention was given to entertainment (24,331; 30 per cent) followed by miscellaneous (19,413; 24.0 per cent) and advertisements (18,112; 22.3 per cent). The Pearson’s chi-square test indicates that there was a significant difference in x2 = 21,765, p-value < 2.2e 16 between the level of coverage of climate change articles on other topics in the selected newspapers. Research limitations/implications – Scanning the sampled six newspapers for climate change information and recording the results in the code sheet for the period of 10 years was a tedious and time consuming exercise which demanded researchers and coders to be extremely careful. Also it is possible that the sampling strategy used led to missing some data that would have resulted into different conclusions about each newspaper’s coverage on climate change. However, the systematic sampling strategy was applied for a long period, that is, 40 months for each newspaper that increased the reliability and accuracy of the results and conclusions about the overall trends in each newspaper’s coverage of climate change information. Practical implications – These findings imply that, as the disseminators of information, Tanzanian newspapers did not pay adequate attention to climate change issues. The study concludes that contrary to the fact that climate change is among the threatening phenomena in Tanzania that would commensurate a significant attention in the media, the findings of this study indicate that the volume of coverage devoted to climate change by the newspapers in Tanzania is very low and disproportionate to the level of threat. This leaves a question on the Tanzanian newspapers’ dedication to reporting climate change information. It is therefore recommended that newspapers’ media owners, editors and journalists should be environmental nationalistic enough to frequently report climate change information, and the scope of the government-owned newspapers should be revisited to ensure more coverage of climate change information in their publication which can be done by having a section specifically dedicated for climate change issue. Originality/value – This study has therefore contributed to the growing body of analytical research knowledge on the role of newspapers in the dissemination of climate change information in Tanzania. This study has also highlighted the importance of taking into account newspapers coverage of climate change information which can further be used for policy recommendations to improve the climate change information communication system through the use of newspapers and show the credibility of the newspapers in creating awareness of climate change in Tanzania.